PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SD - Rukmaliani, Utami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to analyze the effect of using inquiry learning model to student’s achievement in natural science learning of grade IV in SDN 27 Sungai Raya Kabupaten Kubu Raya. This research uses Quasy Experiment experimental method with the Nonequivalent Control Group Design research design. The population in this study is all students of class IV SDN 27 Sungai Raya Kabupaten Kubu Raya. The sample in this study is all students of class IVA which amounted to 28 students. The sample selection using probability sampling technique with simple random sampling type. The data collection technique used is the measurement technique. Based on result of data analysis, the mean of student learning achievement in experiment class is 63,04 with standard deviation of 5,5. The result of hypothesis test (t-test) using t-test Polled Varian obtained count 3,093 and tabel 2,007 (significant level (α) = 5% and dk 52) shows count is bigger than table then Ha is accepted. From the calculation of Effect Size (ES), obtained 0.49 (medium criterion). This means that inquiry learning model has an effect on the result of Natural Science learning of grade IV in SDN 27 Sungai Raya Kabupaten Kubu Raya. Keywords: Effect, Inquiry Learning Model, Student’s Achievement, Natural Sciences Learning